Oxidative stress and hypoxia parameters in children with nephrotic syndrome - Ievgeniia Burlaka (Ukrainian Journal of Nephrology and Dialysis, 2025)
Nephrotic syndrome (NS) is a kidney disorder caused by increased permeability of the glomerular filtration barrier. The diagnosis is based on four main clinical features: edema, hyperlipidemia, hypoalbuminemia, and proteinuria. The pathogenesis of NS is linked to multiple pathways, including inflammation and apoptosis. The present study aimed to assess oxidative stress and hypoxia parameters in children with NS.Methods. This cross-sectional study included 88 patients with NS at different stages of chronic kidney disease (CKD) and 25 healthy individuals (control group). Plasma samples were used to measure intracellular hypoxia-inducible factor alpha (HIF-1α) and manganese superoxide dismutase (Mn-SOD). The levels of superoxide radicals were assessed using the electron paramagnetic resonance (EPR) method. ANOVA, followed by the post hoc Kruskal-Wallis test for multiple comparisons, was used to determine statistical significance. Statistical analysis was performed using Past4 software for Windows. A p-value <0.05 was considered statistically significant.Results. A significant increase in the generation rate of superoxide radical anions (O₂⁻•) by neutrophils was detected in all children with NS (1.55±0.7 nmol/1×10³ cells/min in the CKD I stage group and 2.79±0.22 nmol/1×10³ cells/min in the CKD II–III stage group, p<0.01). The expression of Mn-SOD was reduced to 76.57±4.62% in the CKD I stage group and further decreased to 59.03±3.23% in the CKD II–III stage group, compared to the control group (p<0.01 and p<0.001, respectively). Individual analysis of plasma HIF-1α levels and Mn-SOD levels revealed a significant inverse correlation between these biomarkers (r=-0.71, p<0.0001, CI: -0.8003 to -0.5878).Conclusions. This study demonstrates that oxidative stress activation leads to a significant reduction in antioxidative capacity in children with nephrotic syndrome. An inverse correlation was observed between Mn-SOD levels and plasma HIF-1α levels, suggesting a potential interplay between oxidative stress and hypoxia in NS pathogenesis.